Platelet Granule Exocytosis: A Comparison with Chromaffin Cells - Fitch-Tewfik, Jennifer; Flaumenhaft, Robert (Frontiers in Endocrinology, 2013)
The rapid secretion of bioactive amines from chromaffin cells constitutes an important component of the fight or flight response of mammals to stress. Platelets respond to stresses within the vasculature by rapidly secreting cargo at sites of injury, inflammation, or infection. Although chromaffin cells derive from the neural crest and platelets from bone marrow megakaryocytes, both have evolved a heterogeneous assemblage of granule types and a mechanism for efficient release. This article will provide an overview of granule formation and exocytosis in platelets with an emphasis on areas in which the study of chromaffin cells has influenced that of platelets and on similarities between the two secretory systems. Commonalities include the use of transporters to concentrate bioactive amines and other cargos into granules, the role of cytoskeletal remodeling in granule exocytosis, and the use of granules to provide membrane for cytoplasmic projections. The SNAREs and SNARE accessory proteins used by each cell type will also be considered. Finally, we will discuss the newly appreciated role of dynamin family proteins in regulated fusion pore formation. This evaluation of the comparative cell biology of regulated exocytosis in platelets and chromaffin cells demonstrates a convergence of mechanisms between two disparate cell types both tasked with responding rapidly to physiological stimuli.